Asymmetric Michael addition reactions of pyrrolones with chalcones catalyzed by vicinal primary-diamine salts. Issue 39 (5th May 2017) - Du, Xiaolei; Yin, Dawei; Ge, Zemei; Wang, Xin; Li, Runtao
Abstract : The asymmetric Michael addition reaction of pyrrolones with chalcones catalyzed by vicinal primary-diamine salts has been developed in good yields and high enantioselectivities. Abstract : The efficient asymmetric Michael addition reactions of pyrrolones with chalcones catalyzed by a simple and commercially available chiral 1, 2-diaminocyclohexane-2-( N -Boc-amino)benzoic acid have been developed to provide the corresponding Michael adducts in good yields (up to 90%) and high enantioselectivities (up to 95% ee).